Genetic Variability in Distinct Genotypes of Forage Pearl Millet (Pennisetum glaucum (L.) R. Br.) for Forage Yield and Forage Yield Attributing Traits - Sharma, Ritu; Viradiya, Y. A.; Donga, A. R.; Parsaniya, T. A.; Beniwal, Jogender; Jivan, Patel Parth (International Journal of Economic Plants, 2024)
The experiment was conducted during kharif (July–October, 2023) at Centre for Forage Research, S. D. Agricultural University, Sardarkrushinagar, Gujarat, India to study to appraise genetic variability in pearl millet genotypes for fodder yield and associating traits. Thirty forage pearl millet genotypes were evaluated for genetic parameters in terms of days to flowering, days to maturity, plant height (cm), number of tiller plant-1, stem thickness (cm), number of leaf plant-1, leaf length (cm), leaf: stem ratio, dry fodder content (%), dry fodder yield plant-1 (g), crude protein content (%), green forage yield plant-1 (g). Range, mean, phenotypic coefficient of variation (PCV), genotypic coefficient of variation (GCV), heritability, and genetic advance as per cent of mean were studied. The phenotypic coefficient of variation was higher than the genotypic coefficient of variation for all the traits indicating slight dominance of environment in the expression as compared to genetic contribution. Genotypic and phenotypic coefficient of variation were high for green forage yield plant-1, dry fodder yield plant-1, plant height, and number of tiller plant-1. The high heritability with high genetic advance as a per cent of mean has been observed for green forage yield plant-1, crude protein content, dry fodder yield plant-1, leaf: stem ratio, leaf width, number of leaves plant-1, plant height, number of tiller plant-1, and stem thickness. This indicated that there is a lesser influence of environment in the expression of these traits and are predominantly governed by additive genes in their inheritance and selection for these traits will be effective for improvement of both forage yield and quality.